2022
DOI: 10.1037/ccp0000555
|View full text |Cite
|
Sign up to set email alerts
|

Personalized prescriptions of therapeutic skills from patient characteristics: An ecological momentary assessment approach.

Abstract: Objective: Rather than relying on a single psychotherapeutic orientation, most clinicians draw from a range of therapeutic approaches to treat their clients. To date, no data-driven approach exists for personalized predictions of which skill domain would be most therapeutically beneficial for a given patient. The present study combined ecological momentary assessment (EMA) and machine learning to test a data-driven approach for predicting patient-specific skilloutcome associations.Method: Fifty (Mage= 37 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The articles included in this special issue underscore this diversity of precision/tailoring aims. The studies by Webb et al (2021) and Bruijniks et al (2021) targeted evidence-based selection of the most effective treatment for a given individual. Webb et al (2021) demonstrated how two treatments that are equally effective at the sample level, behavioral therapy (BT) and dialectical behavioral therapy (DBT), can show distinct efficacy levels for each individual patient.…”
Section: What Do We Want To Achieve?mentioning
confidence: 99%
See 4 more Smart Citations
“…The articles included in this special issue underscore this diversity of precision/tailoring aims. The studies by Webb et al (2021) and Bruijniks et al (2021) targeted evidence-based selection of the most effective treatment for a given individual. Webb et al (2021) demonstrated how two treatments that are equally effective at the sample level, behavioral therapy (BT) and dialectical behavioral therapy (DBT), can show distinct efficacy levels for each individual patient.…”
Section: What Do We Want To Achieve?mentioning
confidence: 99%
“…The studies by Webb et al (2021) and Bruijniks et al (2021) targeted evidence-based selection of the most effective treatment for a given individual. Webb et al (2021) demonstrated how two treatments that are equally effective at the sample level, behavioral therapy (BT) and dialectical behavioral therapy (DBT), can show distinct efficacy levels for each individual patient. Hence, the authors sought to develop an evidence-based tool for selecting the treatment expected to show the optimal outcome for each patient.…”
Section: What Do We Want To Achieve?mentioning
confidence: 99%
See 3 more Smart Citations